2003
DOI: 10.1046/j.1320-5331.2003.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and spatial variation in algal growth potential and growth‐limiting nutrients in a shallow endorheic lake: Lake Pátzcuaro (Mexico)

Abstract: The present research focused on the functional role of the phytoplankton of an economically important endorheic tropical lake from the perspective of algal growth bioassays. The algal growth potential of the lake water was compared for littoral and pelagic sites during the wet and dry seasons. Algal growth potentials at open waters reached minimum and maximum values following the seasonal alternation of dilution (by rain) and concentration (by evaporation) respectively. Conversely, at southern littoral station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
0
12
1
5
Order By: Relevance
“…It also resuspends sediments in the littoral, the source for the large diatoms. Phytoplankton is suppressed through rainfall directly on the lake surface, turbidity, and nutrient dilution (Bernal-Brooks et al 2003; Oliva et al 2001). With decreasing rainfall and temperatures in fall, the water column mixes and a second bloom of algae occurs, probably benefiting from recycled nutrients and improved light conditions after reduction of the suspended matter.…”
Section: Seasonality Of the Laminae And Varve Formationmentioning
confidence: 99%
“…It also resuspends sediments in the littoral, the source for the large diatoms. Phytoplankton is suppressed through rainfall directly on the lake surface, turbidity, and nutrient dilution (Bernal-Brooks et al 2003; Oliva et al 2001). With decreasing rainfall and temperatures in fall, the water column mixes and a second bloom of algae occurs, probably benefiting from recycled nutrients and improved light conditions after reduction of the suspended matter.…”
Section: Seasonality Of the Laminae And Varve Formationmentioning
confidence: 99%
“…Contrary to the concept of a single limiting nutrient, the concept of N and P co-limitation has been put forward by various researchers Wurtsbaugh 2008, Sterner 2008). Co-limitation of N and P was found in Lake Pátzcuaro in Mexico (Bernal-Brooks et al 2003); in 63% of 30 small upland lakes in Cumbria, Wales, Scotland, and Northern Ireland (Maberly et al 2002); in 2 warm temperate Texan reservoirs (Sterner andGrover 1998, Grover et al 1999); and in reservoirs in Kansas, USA (Dzialowski et al 2005). In a study of 8 mountain lakes of central Colorado, 79% of all observed instances of limitation indicated that N was the most frequently limiting nutrient, either alone or in combination with P (Morris and Lewis 1988).…”
Section: Introductionmentioning
confidence: 99%
“…En los últimos años, la gran diversidad de especies que conforman el fitoplancton en sistemas lacustres, ha sufrido importantes descensos causados directa o indirectamente por las actividades humanas (Prosperi, 2002;Bernal-Brooks et al, 2003). La comunidad de fitoplancton es sensible a los cambios ambientales, por lo que la alteración de su hábitat, causada por la contaminación, es probable que sea una causa directa de su declive (Dávalos et al, 1989).…”
Section: Introductionunclassified
“…En el caso de algunas presas, el fitoplancton con certeza ha tenido una reducción drástica en sus poblaciones y en su riqueza específica, debido a la transformación del hábitat, tanto por causas naturales como antropogénicas (Dávalos et al, 1989;Prosperi, 2002;Bernal-Brooks et al, 2003;Jasprica et al, 2005).…”
Section: Introductionunclassified
See 1 more Smart Citation